Peran Guru Pendidikan Agama Islam Dalam Mengembangkan Self-Control Siswa Kelas VIII SMPI At-Tablighiyah Desa Ponjanan Timur Kecamatan Batumarmar, Pamekasan - Rukmiyati Rukmiyati; Moh. Dannur; Fajriyah Fajriyah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
This study aims to examine and understand more deeply the existence of the role of PAI teachers in developing students' self-control in order to be able to regulate and direct and counteract all forms of behavior that have the potential to bring negative currents that are at odds with the standards of ethical and moral norms in establishing socialized interactions so that they are agile in predicting well at any time obstacle factors arise affecting unwanted intrusive behavior to be faced and align themselves psychologically and physically in actual conditions with the availability of supporting elements in providing understanding of knowledge, appreciation and experience so that students become adolescents who continue to develop in terms of faith and devotion. This research uses a qualitative approach of case study type by involving PAI teachers, 8th grade students and school principals as key informants.Data was gathered through observation, interviews, and documentation. The results showed that efforts in the role of Islamic religious education teachers to develop student self-control through revamping the seating model of innovative learning group discussions, educating with exemplary values, inviting active communication, providing motivation and appreciation, fostering and guiding with a disciplined attitude and establishing cooperation with the principal through giving responsibility to students and providing personal guidance services by utilizing the availability of adequate facilities and infrastructure and the principal's participation in optimizing religious activities through the cooperation of parents in monthly meeting activities to anticipate students who are difficult to work with and lack of parental attention and affection and the influence of mass media is expected to foster good self-control in self-implementation and daily life.